2019
DOI: 10.1021/acs.jpcc.8b10362
|View full text |Cite
|
Sign up to set email alerts
|

Nonhexagonal Na Sublattice Reconstruction in the Super-Ionic Conductor Na2Zn2TeO6: Insights from Ab Initio Molecular Dynamics

Abstract: In this work, we examine the distribution of Na+ ions in the interlayer of the super-ionic conductor Na2Zn2TeO6 by means of atomistic first-principle modeling based on density functional theory. This layered structure presents a variety of partially occupied interstitial Na sites forming a triangular prismatic coordination group with the neighboring O atoms. We examine the energetics of Na periodic arrangements, considering distinct occupation patterns of these interstitial sites. We then simulate high-tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 39 publications
(59 reference statements)
0
28
0
Order By: Relevance
“…9. 15,59,90,173,[249][250][251][252][253][254][255]257,258 Experimentally, the measurement of ionic conductivity is conducted via linear response techniques with polarised electromagnetic fields such as electrochemical impedance spectroscopy (EIS). 259 EIS entails applying a low amplitude low frequency oscillating Fig.…”
Section: Solid-state Ion Diffusion In Honeycomb Layered Oxidesmentioning
confidence: 99%
See 2 more Smart Citations
“…9. 15,59,90,173,[249][250][251][252][253][254][255]257,258 Experimentally, the measurement of ionic conductivity is conducted via linear response techniques with polarised electromagnetic fields such as electrochemical impedance spectroscopy (EIS). 259 EIS entails applying a low amplitude low frequency oscillating Fig.…”
Section: Solid-state Ion Diffusion In Honeycomb Layered Oxidesmentioning
confidence: 99%
“…9 Solid-state diffusive properties of typical cations sandwiched between honeycomb slabs of various layered oxides showing values of ionic conductivity attained in honeycomb layered oxides at room temperature and also at high temperature (300 1C). 59,90,173,[249][250][251][252][253][254][255] Honeycomb layered oxides based on tellurates generally tend to show high ionic conduction, owing to the partial occupancy of alkali atoms in distinct crystallographic sites that facilitate rapid hopping diffusion mechanism. Inset shows the plot of the dependency of (normalised) conductance s to (normalised) thermal energy k B T of the cations determined by linear response of the diffusion current to low amplitude, slowly oscillating voltage by electrochemical impedance spectroscopy (EIS).…”
Section: Solid-state Ion Diffusion In Honeycomb Layered Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, theoretical and experimental studies to investigate the structural disorders particularly on the aforementioned O-type and P-type Na honeycomb layered oxides have been commissioned in an attempt to draw correlations between the atomic structure (microscopic details) with macroscopic manifestations such as electrochemical performance and phase transitions. [44][45][46] Recent studies utilising TEM on the O3-type Na3Ni2SbO6 have revealed the existence of disordered sequences in the arrangement of Ni and Sb atoms as a possible reason behind phase transitions and improved ion mobility. [44] Even though, P-type Na2M2TeO6 would make an ideal platform for investigating structural revolutions on pristine cathodes, crystallography studies on these materials lack rigour with literature limited only to theoretical computations and XRD analyses conducted on Na2M2TeO6.…”
Section: Introductionmentioning
confidence: 99%
“…[44] Even though, P-type Na2M2TeO6 would make an ideal platform for investigating structural revolutions on pristine cathodes, crystallography studies on these materials lack rigour with literature limited only to theoretical computations and XRD analyses conducted on Na2M2TeO6. [45][46][47] As such, information pertaining the local atomistic structures (TEM) and emergent attributes remain elusive.…”
Section: Introductionmentioning
confidence: 99%